Polymedication Electronic Monitoring System (POEMS) – a new technology for measuring adherence - Arnet, Isabelle; Walter, Philipp N.; Hersberger, Kurt E. (Frontiers in Pharmacology, 2013)
Introduction: Reliable and precise measurement of patient adherence to medications is feasible by incorporating a microcircuitry into pharmaceutical packages of various designs, such that the manoeuvres needed to remove a dose of drug are detected, time-stamped, and stored. The principle is called "electronic medication event monitoring" but is currently limited to the monitoring of a single drug therapy. Aim: Introducing a new technology; a clear, self-adhesive polymer film, with printed loops of conductive wires that can be affixed to multidrug punch cards for the electronic adherence monitoring of multiple medication regimens (POEMS); illustrating potential benefits for patient care. We present a preliminary report with one patient experience. Materials and methods: Our illustrative case was supplied with a prefilled 7-day multiple medication punch card with unit-of-use doses for specific times of the day (6 pills in the morning cavity, 2 pills in the evening cavity and 1 pill in case of insomnia in the bedtime cavity), with the new electronic film affixed on it. Results: The intake times over 1 week were extremely skewed (median intake hours at 2:00 pm for the morning doses and at 6:40 pm for the evening doses). After an intervention aimed at optimising the timing adherence, the morning and evening intake hours became more balanced, with 42.3% of correct dosing intervals (± 3h) for drugs with twice daily intake (vs. 0% before the intervention). Discussion: The electronic monitoring of the entire therapy revealed an intake pattern that would have remained undiscovered with any other device and allowed a personalized intervention to correct an inadequate medication intake behavior. POEMS may guide health professionals when they need to optimise a pharmacotherapy because of suspected insufficient adherence. Further, knowing the intake pattern of the entire pharmacotherapy can elucidate unreached clinical outcome, drug-drug interactions, and drug resistance. In the